Intelligent Production of Wire Bonds using Multi-Objective Optimization – Insights, Opportunities and Challenges - Unger, Andreas; Hunstig, Matthias; Meyer, Tobias; Brökelmann, Michael; Sextro, Walter (In Proceedings of IMAPS 2018 – 51st Symposium on Microelectronics, Pasadena, CA, 2018)
Ultrasonic wire bonding is an indispensable process in the industrial manufacturing of semiconductor devices. Copper wire is increasingly replacing the well-established aluminium wire because of its superior electrical, thermal and mechanical properties. Copper wire processes differ significantly from aluminium processes and are more sensitive to disturbances, which reduces the range of parameter values suitable for a stable process. Disturbances can be compensated by an adaption of process parameters, but finding suitable parameters manually is difficult and time-consuming. This paper presents a physical model of the ultrasonic wire bonding process including the friction contact between tool and wire. This model yields novel insights into the process. A prototype of a multi-objective optimizing bonding machine (MOBM) is presented. It uses multi-objective optimization, based on the complete process model, to automatically select the best operating point as a compromise of concurrent objectives.
Keywords: wire bonding; multi-objective optimization; process model; copper wire; self-optimization

Hierarchical nanopores formed by block copolymer lithography on the surfaces of different materials pre-patterned by nanosphere lithography - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg (Nanoscale)
Bottom-up patterning techniques allow for the creation of surfaces with ordered arrays of nanoscale features on large areas. Two bottom-up techniques suitable for the formation of regular nanopatterns on different length scales are nanosphere lithography (NSL) and block copolymer (BCP) lithography. In this paper it is shown that NSL and BCP lithography can be combined to easily design hierarchically nanopatterned surfaces of different materials. Nanosphere lithography is used for the pre-patterning of surfaces with antidots, i.e. hexagonally arranged cylindrical holes in thin films of Au, Pt and TiO2 on SiO2, providing a periodic chemical and topographical contrast on the surface suitable for templating in subsequent BCP lithography. PS-b-PMMA BCP is used in the second self-assembly step to form hexagonally arranged nanopores with sub-20 nm diameter within the antidots upon microphase separation. To achieve this the microphase separation of BCP on planar surfaces is studied, too, and it is demonstrated for the first time that vertical BCP nanopores can be formed on TiO2, Au and Pt films without using any neutralization layers. To explain this the influence of surface energy, polarity and roughness on the microphase separation is investigated and discussed along with the wetting state of BCP on NSL-pre-patterned surfaces. The presented novel route for the creation of advanced hierarchical nanopatterns is easily applicable on large-area surfaces of different materials. This flexibility makes it suitable for a broad range of applications, from the morphological design of biocompatible surfaces for life science to complex pre-patterns for nanoparticle placement in semiconductor technology.

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)
Dodecyl amine edge functionalized few-layer graphene oxide quantum dots were synthesized in good yields. The covalent functionalization was demonstrated with NMR and AFM-IR. The resulting structure and particle size was measured with AFM and HRTEM. The thermal stability of the compound was investigated and showed a stability of up to 220 °C. The modified graphene oxide quantum dots showed excellent solubility in various organic solvents, including ethers, methanol, toluene, n-hexane, heptane, xylene, dichloromethane and toluene. The stability of a resulting toluene solution was also proven by static light scattering measurements over several days. The excellent solubility gives the possibility of an efficient and fast spray application of the functionalized graphene oxide quantum dots to steel surfaces. Hence, the macroscopic friction behavior was investigated with a Thwing-Albert FP-2250 friction tester. A thin film of the dodecyl amine functionalized graphene oxide quantum dots on steel lowered the friction coefficient from 0.17 to 0.11 and revealed a significant corrosion inhibition effect.

Easily Accessible Protein Nanostructures via Enzyme Mediated Addressing - Rüdiger, Arne A.; Brassat, Katharina; Lindner, Jörg; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Site-specific formation of nanoscaled protein structures is a challenging task. Most known structuring methods are either complex and hardly upscalable or do not apply to biological matter at all. The presented combination of enzyme mediated autodeposition and nanosphere lithography provides an easy-to-apply approach for the buildup of protein nanostructures over a large scale. The key factor is the tethering of enzyme to the support in designated areas. Those areas are provided via prepatterning of enzymatically active antidots with variable diameters. Enzymatically triggered protein addressing occurs exclusively at the intended areas and continues until the entire active area is coated. After this, the reaction self-terminates. The major advantage of the presented method lies in its easy applicability and upscalability. Large area structuring of entire support surfaces with features on the nanometer scale is performed efficiently and without the necessity of harsh conditions. These are valuable premises for large-scale applications with potentials in biosensor technology, nanoelectronics, and life sciences.

With directed self-arrangement of DNA origami to large-area quantum dot arrays - Grundmeier, Guido; Brassat, Katharina; Keller, A.; Lindner, Jörg

Hierarchical nanopore and nanoring arrays by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Lindner, Jörg

Ti-6Al-4V alloy: 3D printing of lightweight implants and nanopatterning by self-assembly - Brassat, Katharina; Taube, A.; Kool, Daniel; Tasche, L.; Hoyer, K.P.; Schaper, Mirko; Lindner, Jörg

Morphology investigation of nanopores by block copolymer lithography on different material surfaces - Brassat, Katharina; Kool, Daniel; Taube, A.; Schaper, Mirko; Lindner, Jörg

Nanoscopic protein arrays on BCP prepatterned surfaces - Brassat, Katharina; Brüngeler, A.; Bremser, W.; Strube, O.I.; Lindner, Jörg

Hierarchical nanopatterns by site-selective DNA origami adsoprtion on pre-patterned surfaces - Brassat, Katharina; Ramakrishna, S.; Keller, A.; Lindner, Jörg